Everyday Life – Between Rationality of Actions and Authority. An Example of Social Diagnosis by Erich Fromm - Paszenda, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
In accordance with the sociological concept of the world by Alfred Schütz, the world of everyday life constitutes the object of activities and interactions of given individuals, who – in turn – have to gain control over it but also modify it in order to accomplish their own goals, within the framework of such world and amongst others. In such a context, it comes across as particularly interesting to recognize whether the contemporary man acts according to their own needs, desires and goals, and what role authority has in their own activities. This article attempts to answer these questions on the basis of the social diagnosis carried out by the American psychologist and sociologist Erich Fromm.
Keywords: Fromm, Erich (1900-1980)